A new approach to physically based interpretation of experimental data in 2D problems in mechanics - Karmowski, Wojciech; Midura, Grzegorz (Computer Assisted Methods in Engineering and Science, 2022)
The concept of experimental data interpretation in mechanics using Dirac function is presented. The objective is to find general differential equation, which may be used to approximate the stress field sought. Application of this method may convert problem from general spline to variational one. Basic idea has been presented earlier in [6] where both theoretical data and results of experiments have been taken into account. Here, the method has been used to solve a 2D problem. Numerical tests performed for both generated and experimental data proved its usefulness.